Reverse Osmosis Coupled with Ozonation for Clean Water Recovery from an Industrial Effluent: Technical and Economic Analyses - Ivette Montero-Guadarrama; Claudia Muro Urista; Gabriela Roa-Morales; Edith Erialia Gutiérrez Segura; Vianney Díaz-Blancas; Germán Eduardo Dévora-Isiordia; Jesús Álvarez-Sánchez (Membranes)
Technical and economic criteria were used to evaluate the feasibility of the treatment of an industrial effluent (10 m3/h) for water recovery and reuse. The treatment evaluation included the following: (1) effluent characteristic determination; (2) selection and evaluation of the effluent treatment at lab scale, establishing operating conditions and process efficiency; (3) scaling up the treatment process to the industrial level; (4) treatment plant design and commercial availability analysis of the required equipment; and (5) the costs of the inversion and operation of the plant treatment, cost/m3 for water recovery, and time of investment recovery. The physicochemical characteristics of the effluent exposed the polluted wastewater with sodium chloride salts and colourants, predominating a mixture of tartrazine, Red 40, and brilliant blue from the synthesis of food additives. Other contributions of organic compounds and salts could be in minor content. According to the effluent conditions, a coupled process, integrated with ozonation and reverse osmosis, was indicated to be a treatment for water recovery. Scaling up the plant treatment design resulted in 130 m2 of area, producing 7.7 m3/h of clean water. The cost of the effluent treatment was 1.4 USD/m3, with an inversion return of 3.4 years and cost investment of USD 860,407. The treatment process resulted a viable project for water recovery.